The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.